PENGARUH PENGGUNAAN GADGET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III DI SEKOLAH DASAR MEDAN - Tanjung, Darinda Sofia; Sembiring, Ribka Kariani; Habeahan, Dina Finiel (Universitas Negeri Medan, 2022)
The purpose of this study is to ascertain how the use of technology affects the learning outcomes of Class III students at St. Petrus Private Elementary School Medan. This study's participants were all third-graders at Medan's St. Petrus Private Elementary School, which had three classes with 100 students each. Class IIIC was chosen as a sample of 30 students for this study, and the method of sample collection that was used was simple random sampling. A survey-type quantitative approach is utilized in this study. to use the product moment correlation t test to test the hypothesis. According to the findings, the use of gadgets received an average score of 80.17 in the high category, while learning outcomes received an average score of 74 in the lower category. This is supported by the results of the hypothesis t test. If the value of t_count > t_table is 6.809 > 1.697, then Ha is accepted, indicating that third-grade students at St. Petrus Private Elementary School in Medan benefit significantly from the use of technology.